Effectiveness and responses of using Melayu Riau culture-based teaching materials in IPAS learning at SDN 189 Pekanbaru - Guslinda; Munjiatun; Intan Kartika Sari; Beny Al Fajar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Analysing instructional material needs in elementary science education is crucial to ensure alignment with student developmental characteristics and the current curriculum. This research aims to evaluate the effectiveness of teaching materials grounded in the Melayu Riau cultural context for IPAS (Ilmu Pengetahuan Alam dan Sosial) in fifth-grade elementary classrooms. Additionally, the study seeks to assess the perceptions of both teachers and students regarding the implementation of these culturally-based materials. A quantitative quasi-experimental approach was employed, utilising a one-group pretest-posttest design. Data were collected through student assessments administered before and after the intervention, complemented by questionnaires completed by teachers and students to gather feedback on using the teaching materials. The findings revealed that the normality tests for the pretest (α = 0.178) and post-test (α = 0.086) produced values greater than the threshold of α = 0.05, indicating that the data were normally distributed. The average student score increased from 64.48 on the pretest to 80.57 on the post-test. Furthermore, the N-Gain score analysis yielded a value of 0.5277, categorised as medium, demonstrating a moderate improvement in student learning outcomes. Teacher responses to using the Melayu Riau culture-based IPAS teaching materials averaged a score of 82.97, classified as "Very Good." Similarly, student responses averaged 83.2, within the "Very Good" category. These results suggest incorporating local cultural elements into science teaching materials can positively influence student engagement and academic achievement in IPAS for fifth-grade students.